Several Judges' Considerations in Deciding Marriage Dispensation Cases: Case Study at the Rembang Religious Court - M Nur Kholis (International Journal of Social Service and Research, 2023)
This research discusses the problem of early marriage in Rembang, with a focus on marriage dispensation letters submitted to the Rembang Religious Court. Data shows that there are many cases of marriage dispensation, with 52 cases resolved in 2016, an average of more than 6 cases per month. This early marriage is triggered by various factors, including pregnancy out of wedlock due to uncontrolled relationships. The parents of both parties agreed to submit a request for dispensation to the court to allow marriage at an age that does not meet the provisions of the law. This research uses various techniques and data sources, including interviews, primary, secondary, and tertiary data analysis, as well as a literature study. The collected data was analyzed using empirical methods. The research results show that early marriage in Rembang is influenced by cultural, socio-economic, family environment, social, and psychological factors. Customs also play a role in the phenomenon of early marriage.